1997
DOI: 10.1381/096089297765555539
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Banded Gastroplasty: First Experience in Russia

Abstract: The impression of VBG is favorable; however, gaining further experience with the standard techniques and increasing the long-term results are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The dramatic effect of obesity surgery on the MS in this study is not astonishing, because numerous studies have observed the resolution of diabetes mellitus in addition to the desired weight loss after obesity surgery. [27][28][29] The resolution of other obesityrelated conditions has also been observed, such as hypertension 30 and hyperlipidemia. 31 Because diabetes, hypertension, and hyperlipidemia compose the triad of MS components, a 95.6% resolution rate of the MS in severely obese patients 1 year after surgery is expected.…”
Section: Resultsmentioning
confidence: 98%
“…The dramatic effect of obesity surgery on the MS in this study is not astonishing, because numerous studies have observed the resolution of diabetes mellitus in addition to the desired weight loss after obesity surgery. [27][28][29] The resolution of other obesityrelated conditions has also been observed, such as hypertension 30 and hyperlipidemia. 31 Because diabetes, hypertension, and hyperlipidemia compose the triad of MS components, a 95.6% resolution rate of the MS in severely obese patients 1 year after surgery is expected.…”
Section: Resultsmentioning
confidence: 98%
“…Control rates for most procedures currently performed vary from 40 to 100%. Gastric bypass and malabsorptive procedures offer the highest rates of remission of T2DM () ( 14 (EL 3), 84 (EL 3), 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 (EL 3–4)) . A shorter duration of T2DM and greater weight loss are independent predictors of T2DM remission ( 130 (EL 3)) .…”
Section: Benefits Of Bariatric Surgerymentioning
confidence: 99%
“…Weight loss stabilizes at 1 year with a mean EWL of approximately 50% to 60%. 77,79,89,90,92,95,[97][98][99][100][101][102][103] Over time, there seems to be slow weight regain, 89,98,[104][105][106] with 50% of the patients maintaining 50% or more EWL at 5 years and 40% EWL at 10 years. 98,104,105 The Mayo Clinic, Rochester, Minn, reported only 26% of the 71 patients maintained an EWL of more than 50% 10 years following VBG.…”
Section: Obesity Surgerymentioning
confidence: 99%
“…Bourdages et al 127 reported the resolution of NIDDM in 5 (83%) of 6 subjects following VBG. Yashkov et al 100 reported the Russian experience with VBG in which 3 of 4 patients with NIDDM had complete resolution of diabetes and the fourth patient experienced improvement in glucose metabolism. Similarly, Haciyanli et al 103 reported resolution of NIDDM in 75% of diabetic patients following VBG.…”
Section: Effects Of the Surgical Procedures For Obesity On Diabetesmentioning
confidence: 99%